2016
DOI: 10.1142/s0219199715500091
|View full text |Cite
|
Sign up to set email alerts
|

Some remarks on modified diagonals

Abstract: We prove a number of basic vanishing results for modified diagonal classes. We also obtain some sharp results for modified diagonals of curves and abelian varieties, and we prove a conjecture of O'Grady about modified diagonals on double covers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Remark 4.11. Proposition 4.9 is also proved in [11], where it is used to deduce the vanishing Γ g+2 (X, a) = 0 of Remark 1.4, for any point a ∈ X, from the main result of Colombo and van Geemen [5].…”
Section: Case Of Curvesmentioning
confidence: 99%
“…Remark 4.11. Proposition 4.9 is also proved in [11], where it is used to deduce the vanishing Γ g+2 (X, a) = 0 of Remark 1.4, for any point a ∈ X, from the main result of Colombo and van Geemen [5].…”
Section: Case Of Curvesmentioning
confidence: 99%
“…• In [Voi15], Voisin showed that if X is a smooth projective connected variety of dimension n swept out by irreducible curves of genus g supporting a zero-cycle rationally equivalent to pt ∈ X, then we have ∆ ′ m = 0 for m ≥ (n + 1)(g + 1). • In [MY16], Moonen and Yin showed that -∆ ′ n = 0 on a g-dimensional abelian variety precisely when n ≥ 2g + 1, and -∆ ′ n = 0 on a curve of genus g whenever n ≥ g + 2 (which is sharp for a generic pointed curve, see [Qiz14]). We will show that the minimal k ≤ m such that ∆ ′ k = 0 determines the Z-linear relations between the n m classes ∆ A (A) ∈ A • (X n ) Q for A ⊂ {1, .…”
Section: Introductionmentioning
confidence: 99%